Optimizing Science Learning Through Workshops of STEM-Project-Based Learning on Merdeka Curriculum: Optimalisasi Pembelajaran IPA Melalui Workshop STEM-Project Based Learning Berbasis Kurikulum Merdeka - Kade, Amiruddin; Ningsih, Purnama; Mubarik, Mubarik; Zaky, Muhammad; Rahma, Nur; Kaipal, Kaipal (Yayasan Ahmar Cendekia Indonesia, 2024)
The goal of the STEM with project-based learning workshop at the MGMP IPA Oryza Sativa, Poso Regency, is to enhance the skills of science teachers by developing STEM-based learning that aligns with the Merdeka curriculum. Junior high school science teachers, members of the Oryza Sativa IPA Subject Teachers' Conference (MGMP) in Poso Regency, attended this workshop. The workshop outcomes indicated a commendable enhancement in the proficiency of science instructors in implementing STEM-based learning orientated to the along with the Merdeka curriculum. Science teachers also demonstrated awareness and proficiency in integrating STEM concepts and the Merdeka curriculum into science learning. Therefore, we anticipate that this workshop will enhance the quality of science education at the MGMP IPA Oryza Sativa, Poso Regency. Abstrak Peningkatan keterampilan guru IPA melalui workshop STEM-project based learning berorientasi kurikulum Merdeka di MGMP IPA Oryza Sativa Kabupaten Poso bertujuan untuk meningkatkan kapasitas guru IPA dalam mengembangkan pembelajaran yang berbasis STEM dan berorientasi kurikulum Merdeka. Workshop ini diikuti oleh guru-guru IPA Sekolah Menegah Pertama yang terhimpun pada Musyawarah Guru Mata Pelajaran (MGMP) IPA Oryza Sativa Kabupaten Poso. Hasil dari workshop ini menunjukkan bahwa terdapat peningkatan kapasitas guru IPA dalam mengembangkan proses pembelajaran yang berbasis STEM dan berorientasi kurikulum Merdeka. Guru IPA juga menunjukkan kesadaran dan kemampuan dalam mengintegrasikan konsep STEM dan kurikulum Merdeka dalam pembelajaran IPA. Dengan demikian, workshop ini diharapkan dapat meningkatkan kualitas pembelajaran IPA di MGMP IPA Oryza Sativa Kabupaten Poso.